2018
DOI: 10.1590/1516-3180.2017.0272141017
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil): a narrative review

Abstract: BACKGROUND: Carotid intima-media thickness (CIMT), as measured by ultrasound, has been used in large studies as a non-invasive marker for subclinical atherosclerosis. The Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) is a cohort of 15,105 civil servants in six Brazilian cities that included CIMT evaluation in its baseline assessment. The aim of the present narrative review was to provide an overview of ELSA-Brasil CIMT articles published up to July 31, 2017. DESIGN AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
(84 reference statements)
1
5
0
5
Order By: Relevance
“…However, our model can be useful for varying ethnicities and artery types, if the corresponding cIMT progression rates for CCA and male gender are known. We have surveyed and modeled eight different types of ethnicities and three artery types …”
Section: Methodsmentioning
confidence: 99%
“…However, our model can be useful for varying ethnicities and artery types, if the corresponding cIMT progression rates for CCA and male gender are known. We have surveyed and modeled eight different types of ethnicities and three artery types …”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies are widely reported in the literature, [1][2][3][4] and are extremely valuable for improving healthcare practices. Epidemiological information is an instrument for healthcare planning that informs guidelines and improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Na análise da espessura íntima-média carotídeia (EIMC), incluímos todos os participantes do ELSA-Brasil que foram submetidos a este exame na linha de base do estudo e dos quais foram obtidas medidas válidas. Para medir a EIMC, cada artéria carótida comum (ACC) foi identificada ao longo do seu eixo longitudinal, usando brilho e contraste padrão 75 . A medida foi Métodos 25 realizada na parede posterior de um segmento predefinido da ACC de 1,0 cm de comprimento, a partir de 1,0 cm abaixo da bifurcação carotídea, durante três ciclos cardíacos, em área livre de placa aterosclerótica 76 (Figura 3).…”
Section: Critérios De Inclusãounclassified
“…A medida foi Métodos 25 realizada na parede posterior de um segmento predefinido da ACC de 1,0 cm de comprimento, a partir de 1,0 cm abaixo da bifurcação carotídea, durante três ciclos cardíacos, em área livre de placa aterosclerótica 76 (Figura 3). Os valores médios e máximos para cada ACC foram obtidos 75 .…”
Section: Critérios De Inclusãounclassified